2007
DOI: 10.1631/jzus.2007.b0323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromium nanoparticle dosage on growth, body composition, serum hormones and tissue chromium in Sprague-Dawley rats

Abstract: This 6-week study was conducted to evaluate the effects of seven different levels of dietary chromium (Cr) (0, 75, 150, 300, 450, 600, and 1 200 ppb Cr) in the form of Cr nanoparticle (CrNano) on growth, body composition, serum hormones and tissue Cr in Sprague-Dawley (SD) rats. Seventy male SD rats (average initial body weight of (83.2±4.4) g) were randomly assigned to seven dietary treatments (n=10). At the end of the trial, body composition was assessed via dual energy X-ray absorptiometry (DEXA). All rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 33 publications
3
17
0
4
Order By: Relevance
“…In our study, the Cr contents of breast meat and blood were very significantly increased with the inorganic and CEBS supplemented. Our results here showed that the supplemental Cr in CEBS had a significant influence on Cr content of breast muscle in agreement with a previous report [28]. The effect of CEBS was greater than for inorganic Cr in this experiment, suggesting that CEBS had greater bioavailability as a Cr resource.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the Cr contents of breast meat and blood were very significantly increased with the inorganic and CEBS supplemented. Our results here showed that the supplemental Cr in CEBS had a significant influence on Cr content of breast muscle in agreement with a previous report [28]. The effect of CEBS was greater than for inorganic Cr in this experiment, suggesting that CEBS had greater bioavailability as a Cr resource.…”
Section: Discussionsupporting
confidence: 93%
“…CrProp jest absorbowany z dużą skutecznością 40-60% (94,95). Najwyższą akumulację Cr w tkankach wykazano po podaniu Cr w formie nanocząstek (61,105,112).…”
Section: Toksykokinetykaunclassified
“…In mouse, Anderson et al (1989) reported that supplemental chromium resulted in an accumulation of Cr in the liver. Zha et al (2007c) reported that nanoparticles chromium supplementation shown effects on primary tissues such as kidney, liver and hind leg muscle in rats. In addition, Cr has been shown that supplemental chromium led to increased Cr and Zn in serum, liver, kidney and longissimus muscle of laying hens and Japanese quails (Sahin et al, 2002a;Sahin et al, 2002b), but Fe concentrations were not affected in Japanese quails.…”
Section: The Effects Of Various Levels Of Nanocrpic On the Liver And mentioning
confidence: 99%